High-cavity nano-starch, high-aging-resistance rubber material based on high-cavity nano-starch and preparation of high-cavity nano-starch

By gelatinizing and single-helical structure modification of the starch, high-cave nanostarch is prepared and blended with natural latex, the problems of natural rubber aging and poor starch dispersion are solved, and the aging resistance and strength of rubber are significantly improved. High stability and excellent dispersion of rubber materials are achieved.

CN119264282AActive Publication Date: 2025-01-07SOUTH CHINA UNIV OF TECH +1
View PDF 12 Cites 0 Cited by

Patent Information

Application Number
CN202411457178.9
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-10-18
Publication Date
2025-01-07
Estimated Expiration
2044-10-18

AI Technical Summary

Technical Problem

During processing, storage and use, natural rubber is easily aged by environmental factors such as heat oxygen, humidity and heat. The existing anti-aging agents are difficult to disperse evenly, resulting in unstable performance and environmental pollution. The starch native particles are large in size and high in crystallinity, and it is difficult to be in rubber. Evenly dispersed in the middle, resulting in poor anti-aging and reinforcing effects.

Method used

High-cavitation nanostarch is prepared by gelatinizing pretreatment, single helical structure modification treatment, and homogenize it in an ultra-high pressure nanomaterial preparation and disperser, and natural rubber/starch composite materials are prepared by blending natural latex. The high cavity structure is used to enhance the free radical capture ability and dispersion.

Benefits of technology

It significantly improves the aging resistance, tensile strength and tear strength of rubber, avoids the unevenness of anti-aging agents and environmental pollution problems, and at the same time achieves high stability and excellent dispersion of rubber materials.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119264282A_ABST
    Figure CN119264282A_ABST
Patent Text Reader

Abstract

The invention belongs to the technical field of modified rubber, and discloses high-cavity nano starch, a high-aging-resistance rubber material based on the high-cavity nano starch and preparation of the high-cavity nano starch and the high-aging-resistance rubber material. The preparation method of the high-cavity nano starch comprises the following steps: sequentially carrying out gelatinization pretreatment and single-spiral structure modification treatment on starch, and then carrying out homogenization treatment in an ultrahigh-pressure nano material preparation dispersion machine, so as to obtain the high-cavity nano starch. The nano starch emulsion with high stability is prepared by the method, the starch has a high cavity structure, the particle size can reach nanoscale, and the dispersity is remarkably improved when the starch is mixed with natural latex. The high-cavity nano starch can be applied to rubber reinforcement, the tensile strength and tear strength of the obtained rubber material are remarkably improved, the tensile strength is improved by 34%, the tear strength is improved by 58%, and the high-cavity nano starch has excellent aging resistance without adding an anti-aging agent. The problems of non-uniformity, defect increase, discoloration and environmental pollution caused by adding an anti-aging agent into existing rubber are solved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of modified rubber, and particularly relates to a high-cavity nano starch and a high-aging-resistant rubber material based thereon and preparation thereof. Background Art

[0002] Natural rubber has excellent comprehensive properties and processing properties such as wear resistance, high elasticity, and easy processing. It is widely used in industrial products such as tires, conveyor belts, and seals. However, natural rubber and its products are susceptible to aging due to environmental factors such as heat, oxygen, ozone, and humidity during processing, storage, and use. Oxidation is one of the main causes of natural rubber aging. A large number of molecular chains containing carbon-carbon double bonds in natural rubber are prone to produce free radicals under the action of heat and oxygen. The free radicals continue to react with oxygen to break and degrade the main chain of the rubber molecule. At the same time, under the action of free radicals, the residual free sulfur in the sulfur vulcanization system continues to cross-link or desulfurize the polysulfide bonds to produce more single sulfur bonds and disulfide bonds, resulting in a shortened molecular chain and an increase in cross-linking density, which in turn causes the material to become brittle, hard, and lose elasticity. Improving the aging resistance of natural rubber is of great significance for extending its service life and improving its safety in use. Existing technologies mainly improve the aging resistance of natural rubber by adding antioxidants, improving the vulcanization system, etc., but these methods often have a negative impact on the original properties of the rubber. For example, antioxidants are difficult to disperse evenly during the mixing process, resulting in large differences in rubber properties, instability, discoloration of the rubber, and environmental pollution.

[0003] Starch has many advantages such as wide sources, renewable, high cost efficiency, and low environmental impact, especially its large number of active hydroxyl groups, showing great potential for capturing and neutralizing free radicals as a new green rubber antioxidant. However, the original starch particles are large in size, high in crystallinity, and easy to agglomerate, making it difficult to disperse evenly in the rubber matrix, resulting in poor anti-aging and reinforcement effects. Summary of the invention

[0004] In order to overcome the above-mentioned shortcomings and deficiencies of the prior art, the primary purpose of the present invention is to provide a method for preparing high-cavity nano starch.

[0005] The method of the invention firstly processes starch to obtain modified starch with a single helical structure, and then uses an ultra-high pressure nano material preparation disperser to homogeneously disperse the treated starch to prepare nano-scale high-cavity nano starch.

[0006] The preparation method of the invention is green and environmentally friendly, has a specific reaction and strong operability, and has inspiring significance for providing a new type of rubber filler and the preparation and application of green rubber.

[0007] Another object of the present invention is to provide high-cavity nano-starch prepared by the above method.

[0008] Another object of the present invention is to provide a natural latex / starch composite based on the high-cavity nano starch.

[0009] Another object of the present invention is to provide applications of the high-cavity nano-starch, especially in rubber modification.

[0010] Another object of the present invention is to provide a highly aging-resistant rubber material based on the high-cavity nano starch. The natural rubber / starch composite material prepared by blending the high-cavity nano starch of the present invention with natural latex has significantly improved aging resistance.

[0011] The purpose of the present invention is achieved through the following solutions:

[0012] A method for preparing high-cavity nano starch comprises sequentially performing gelatinization pretreatment and single-helix structure modification treatment on starch, and then homogenizing in an ultra-high pressure nano material preparation disperser to obtain high-cavity nano starch.

[0013] In the preparation method of the present invention, the gelatinization pretreatment can be carried out by a conventional gelatinization process, such as preparing a starch suspension with a concentration of 5-25wt% with a phosphate buffer and gelatinizing at 80-100°C for 0.5-1.5h.

[0014] Furthermore, the pH of the phosphate buffer is 5.

[0015] In the preparation method of the present invention, the single helix structure modification treatment may include enzymatic modification, acidic modification or oxidative modification treatment.

[0016] Furthermore, the enzymatic and acid hydrolysis modification treatment includes the following steps: adding amylase after starch gelatinization pretreatment, heat preservation and enzymatic hydrolysis, adding acid solution after heating and inactivation, heating and acid hydrolysis, and obtaining modified starch with a single helical structure after enzymatic and acid hydrolysis.

[0017] Furthermore, the amount of amylase used may be 5-30 ASPU / g starch.

[0018] Furthermore, the heat preservation enzymolysis can be carried out at 55-65°C, and the enzymolysis time can be 4-8h.

[0019] Furthermore, the amylase may be any amylase conventionally used in the art, such as pullulanase, α-glucan phosphorylase, and the like.

[0020] Furthermore, the molar ratio of the acid solution to the starch can be 0.25:1-1:1. The acid solution can be hydrochloric acid, sulfuric acid, phosphoric acid, etc., and the concentration of the acid solution can be 1-3 mol / L.

[0021] Furthermore, the heating acid hydrolysis can be carried out at 70-90° C., and the acid hydrolysis time can be 1-6 hours.

[0022] Furthermore, after the acid hydrolysis, the starch can be neutralized with alkali solution and washed with water to obtain treated starch.

[0023] Furthermore, the oxidative modification treatment is carried out by subjecting the starch after gelatinization pretreatment to an oxidation reaction with copper sulfate and hydrogen peroxide under acidic conditions.

[0024] Furthermore, the amount of copper sulfate used can be 1-3‰ of the mass of starch.

[0025] Furthermore, the molar ratio of hydrogen peroxide to starch used may be 0.15:1-0.5:1.

[0026] Furthermore, the acidic condition refers to a system pH of 5.8-6.2.

[0027] Furthermore, the oxidation reaction can be carried out at 25-50° C. and the reaction time can be 8-24 hours.

[0028] Furthermore, after the reaction is completed, the starch is precipitated with anhydrous ethanol and then washed with water to obtain treated starch.

[0029] In the preparation method of the present invention, before the homogenization treatment, the treated starch is diluted with water to a dispersion with a mass concentration of 0.5-2.5wt%. The homogenization times can be 15-25 times, and the dispersion is homogenized until it emits blue light.

[0030] In the method of the present invention, the starch branch chains are enzymatically removed by amylase, and the amorphous region and the residual crystalline region of the enzymatically hydrolyzed starch are destroyed by acid hydrolysis, so as to shorten the molecular chain length, reduce the molecular weight and the relative crystallinity, and transform the starch molecular chain from a double helix to a single helix structure, form a high cavity including a hydroxyl group, and enhance the free radical capture ability of the starch; or the starch is oxidized by a Fenton-like reagent, so that the starch molecular chain is broken and reorganized, and a new functional group is introduced into the molecular chain to increase the steric hindrance between the molecular chains so that the single molecular chain helix forms a cavity structure, and enhances the free radical capture ability of the oxidized starch; and then an ultra-high pressure nano material preparation disperser is used for homogenization treatment, so as to further reduce the size of the high cavity starch particles, and obtain a nano starch emulsion with high stability.

[0031] The present invention provides a high-cavity nano starch prepared by the above method. The preparation method of the present invention prepares a nano starch emulsion with high stability through gelatinization pretreatment, single helical structure modification treatment, and homogenization treatment. The starch has a high-cavity structure and a particle size of nanometers. When mixed with natural latex, the dispersibility is significantly improved.

[0032] The present invention also provides application of the high-cavity nano starch in rubber modification.

[0033] The present invention also provides a natural latex / starch composite based on the high-cavity nano starch. The latex / starch composite is obtained by mixing the high-cavity nano starch dispersion and natural latex, and then co-coagulating.

[0034] Furthermore, in the natural latex / starch composite, the starch content may be 1-30 wt %.

[0035] Furthermore, the mass concentration of the high-cavity micro-nano starch dispersion can be 0.5-2.5wt%. The high-cavity nano starch dispersion is obtained by the above preparation method.

[0036] Furthermore, the solid content of the natural rubber latex may be 50-70%.

[0037] Furthermore, co-coagulation is a conventional process in the art, and continuous stirring can be performed to uniformly mix the high-cavity nano starch and latex, and then the emulsion is broken and precipitated. After precipitation, the solid is washed with water and dried to obtain a latex / starch complex. The continuous stirring time can be 1-3 hours. It can be vacuum dried at 50°C.

[0038] In the above preparation method, the quality of the dispersion liquid and natural latex used can be determined according to the formula combined with the concentration of the dispersion liquid and the solid content of the natural latex, and then the preparation can be carried out.

[0039] The present invention also provides a highly aging-resistant rubber material based on the high-cavity nano-starch, wherein the components contain 1-30 wt % of the high-cavity nano-starch.

[0040] The present invention also provides a method for preparing the above-mentioned high aging-resistant rubber material, which comprises mixing a high-cavity nano starch dispersion and natural latex, co-coagulating to obtain a latex / starch composite; and then mixing with rubber additives using a traditional rubber processing technology to prepare a natural rubber / starch composite material.

[0041] Furthermore, the rubber additives may be conventional additives, such as stearic acid, zinc oxide, accelerators, sulfur, and the like.

[0042] The rubber material prepared by blending high-cavity nano starch in the present invention has significantly improved tensile strength and tear strength, with the tensile strength increased by 34% and the tear strength increased by 58%, and has excellent aging resistance without adding an antioxidant.

[0043] Compared with the prior art, the present invention has the following advantages and beneficial effects:

[0044] (1) The high-cavity nano starch provided by the present invention has a low molecular weight and low relative crystallinity, and its molecular chain is a single helical structure with a high cavity including hydroxyl groups, and has excellent free radical capture ability.

[0045] (2) The high-cavity nano starch of the present invention has excellent dispersibility and compatibility in the rubber matrix, and the natural rubber / starch composite material prepared by blending it with natural latex has significantly improved aging resistance, tensile strength and tear strength. BRIEF DESCRIPTION OF THE DRAWINGS

[0046] In order to more clearly illustrate the technical solutions of the embodiments of the present invention, the drawings required for use in the embodiments are briefly introduced below. It should be understood that the following drawings only show certain embodiments of the present invention and therefore should not be regarded as limiting the scope. For ordinary technicians in this field, other related drawings can be obtained based on these drawings without creative work.

[0047] Figure 1 This is a scanning electron microscope photograph of the high cavity nano starch in Example 1.

[0048] Figure 2 This is a scanning electron microscope photograph of the high cavity nano starch in Example 4.

[0049] Figure 3 This is the X-ray diffraction curve of the high cavity nano starch in Example 1.

[0050] Figure 4 This is a photo of the sticking roller during the mixing process of the natural latex / pure starch composite in Comparative Example 1. DETAILED DESCRIPTION

[0051] The present invention is further described in detail below in conjunction with examples, but the embodiments of the present invention are not limited thereto. It is necessary to point out that the examples are only used to further illustrate the present invention and cannot be construed as limiting the scope of protection of the present invention. In addition, it should be understood that after reading the content taught by the present invention, a skilled person in the field can make some non-essential improvements and adjustments based on the content of the present invention described above, and these equivalent forms also fall within the scope defined by the claims attached to the present application. The raw materials involved in the present invention can all be purchased from conventional commercial channels. For process parameters not specifically noted, conventional techniques can be referred to. The amount of each component is measured in parts by mass and parts by volume, g, mL.

[0052] The raw materials used in the following examples and comparative examples are as follows:

[0053] Cassava starch: food grade, Shandong Hengren Industry and Trade Co., Ltd.;

[0054] Natural latex: solid content 60%, Chinese Academy of Tropical Agricultural Sciences;

[0055] Pullulanase: P299007, Aladdin.

[0056] Example 1

[0057] (1) Preparation of high-cavity nanostarch

[0058] 100 parts by mass of starch were added to 1000 parts by volume of phosphate buffer solution with pH=5.0, and the mixture was placed in a water bath at 100°C and stirred at 300rpm for gelatinization for 0.5h. After complete gelatinization, the mixture was cooled to 58°C, and a pullulanase solution was added according to the amount of 5 ASPU / g starch. The starch paste was then placed in a water bath at 58°C for enzymolysis for 8h. After the enzymolysis reaction, the water bath temperature was raised to 100°C and heated for 30min to inactivate the enzyme to terminate the reaction. Then 150 parts by volume of hydrochloric acid with a concentration of 1 mol / L was added, and the mixture was hydrolyzed in a water bath at 70°C for 3h. After the reaction was completed, the mixture was neutralized, washed with water, diluted and dispersed in deionized water (solid content was 1%), and homogenized 18 times in an ultra-high pressure nanomaterial preparation disperser to prepare a high-cavity nano starch dispersion. The prepared high-cavity nano starch was observed. Figure 1 This is a scanning electron microscope photograph of the high-cavity nano-starch in Example 1. It can be seen from the figure that its particle size reaches the nanometer level and is well dispersed. Figure 3 : is the X-ray diffraction curve of high-cavity nano starch in Example 1. As can be seen from the figure, the starch is transformed from A-type crystals with a double helix structure to V-type crystals with a high cavity with a single helix structure. h type crystallization, and the relative crystallinity is significantly reduced.

[0059] (2) Preparation of natural latex / starch composites

[0060] 100 parts by mass of 1 wt% high-cavity nano-starch dispersion and 33.4 parts by mass of natural latex with a solid content of 60% were mechanically stirred and blended at room temperature and a rotation speed of 500 rpm for 1 hour to make the starch fully and evenly dispersed in the natural latex, and then demulsified, precipitated, washed with water and dried in a vacuum oven at 50°C for 24 hours to obtain a natural latex / starch composite.

[0061] Example 2

[0062] (1) Preparation of high-cavity nanostarch

[0063] 100 parts by mass of starch were added to 1000 parts by volume of a phosphate buffer solution with a pH value of 5.0, and the mixture was placed in a 90° C. water bath and gelatinized at 350 rpm for 1 hour. After complete gelatinization, the mixture was cooled to 58° C., and a pullulanase solution was added at an amount of 10 ASPU / g of starch. The starch paste was then placed in a 59° C. water bath for enzymolysis for 6 hours. After the enzymolysis reaction was completed, the water bath temperature was raised to 100° C. and then heated for 30 minutes to inactivate the enzyme to terminate the reaction. Then, 150 parts by volume of 2 mol / L hydrochloric acid was added, and the mixture was hydrolyzed in a 75° C. water bath for 2 hours. After the reaction was completed, the mixture was neutralized, washed with water, diluted and dispersed in deionized water (solid content was 1.5%), and homogenized 16 times in an ultra-high pressure nano material preparation disperser to prepare a high cavity nano starch dispersion.

[0064] (2) Preparation of natural latex / starch composites

[0065] 120 parts by mass of 1.5 wt% high-cavity nano-starch dispersion and 33.4 parts by mass of natural latex with a solid content of 60% were mechanically stirred and blended at room temperature and a rotation speed of 500 rpm for 1 hour to allow the starch to be fully and evenly dispersed in the natural latex, and then the mixture was demulsified, precipitated, washed with water, and dried in a vacuum oven at 50°C for 24 hours to obtain a natural latex / starch composite.

[0066] Example 3

[0067] (1) Preparation of high-cavity nanostarch

[0068] 100 parts by mass of starch were added to 1000 parts by volume of a phosphate buffer solution with a pH value of 5.0, and the mixture was placed in a water bath at 85°C and stirred at 400 rpm for gelatinization for 1 hour. After complete gelatinization, the mixture was cooled to 58°C, and a pullulanase solution was added according to 15 ASPU / g of starch. The starch paste was then placed in a water bath at 60°C for enzymolysis for 6 hours. After the enzymolysis reaction was completed, the water bath temperature was raised to 100°C and heated for 30 minutes to inactivate the enzyme and terminate the reaction. Then, 150 parts by volume of 3 mol / L hydrochloric acid was added, and the mixture was hydrolyzed in a water bath at 80°C for 1 hour. After the reaction was completed, the mixture was neutralized, washed with water, diluted and dispersed in deionized water (solid content was 2%), and homogenized 20 times in an ultra-high pressure nano material preparation disperser to prepare a high cavity nano starch dispersion.

[0069] (2) Preparation of natural latex / starch composites

[0070] 150 parts by mass of 2 wt% high-cavity nano-starch dispersion and 33.4 parts by mass of natural latex with a solid content of 60% were mechanically stirred and blended at room temperature and a rotation speed of 500 rpm for 1 hour to allow the starch to be fully and evenly dispersed in the natural latex, and then the mixture was demulsified, precipitated, washed with water, and dried in a vacuum oven at 50°C for 24 hours to obtain a natural latex / starch composite.

[0071] Example 4

[0072] (1) Preparation of high-cavity nanostarch

[0073] 100 parts by mass of starch were added to 1000 parts by volume of phosphate buffer solution with pH=5.0, and gelatinized for 0.5h in a water bath at 85°C and stirred at 350rpm. After complete gelatinization, the mixture was cooled to room temperature, adjusted to pH=5.8 with 0.5mol / L sodium hydroxide solution, and then 1 part by mass of copper sulfate and 11 parts by mass of 30% hydrogen peroxide solution were added. The mixture was oxidized for 12h in a water bath at 25°C and mechanically stirred at 300rpm. After the reaction was completed, the mixture was precipitated with anhydrous ethanol and washed with water, and then diluted and dispersed in deionized water (solid content was 1%), and then homogenized 16 times in an ultra-high pressure nano material preparation disperser to obtain a high-cavity nano starch dispersion. The prepared high-cavity nano starch was observed. Figure 2 This is a scanning electron microscope photograph of the high-cavity nano-starch in Example 4. It can be seen from the figure that its particle size reaches the nanometer level and is well dispersed.

[0074] (2) Preparation of natural latex / starch composites

[0075] 100 parts by mass of 1 wt% high-cavity nano-starch dispersion and 33.4 parts by mass of natural latex with a solid content of 60% were mechanically stirred and blended at room temperature and a rotation speed of 500 rpm for 1 hour to make the starch fully and evenly dispersed in the natural latex, and then demulsified, precipitated, washed with water and dried in a vacuum oven at 50°C for 24 hours to obtain a natural latex / starch composite.

[0076] Example 5

[0077] (1) Preparation of high-cavity nanostarch

[0078] 100 parts by mass of starch were added to 1000 parts by volume of a phosphate buffer solution with a pH value of 5.0, and gelatinized for 0.5 h in a water bath at 85°C and stirring at 350 rpm. After complete gelatinization, the mixture was cooled to 30°C, adjusted to pH value of 6.0 with a 0.5 mol / L sodium hydroxide solution, and then 2 parts by mass of copper sulfate and 15 parts by mass of a 30% hydrogen peroxide solution were added. The mixture was oxidized for 18 h in a water bath at 30°C and mechanically stirred at 300 rpm. After the reaction was completed, the mixture was precipitated with anhydrous ethanol and washed with water, and then diluted and dispersed in deionized water (solid content was 1.5%). The mixture was then homogenized 18 times in an ultra-high pressure nano material preparation disperser to obtain a high cavity nano starch dispersion.

[0079] (2) Preparation of natural latex / starch composites

[0080] 120 parts by mass of 1.5 wt% high-cavity nano-starch dispersion and 33.4 parts by mass of natural latex with a solid content of 60% were mechanically stirred and blended at room temperature and a rotation speed of 500 rpm for 1 hour to allow the starch to be fully and evenly dispersed in the natural latex, and then the mixture was demulsified, precipitated, washed with water, and dried in a vacuum oven at 50°C for 24 hours to obtain a natural latex / starch composite.

[0081] Example 6

[0082] (1) Preparation of high-cavity nanostarch

[0083] 100 parts by mass of starch were added to 1000 parts by volume of a phosphate buffer solution with a pH value of 5.0, and gelatinized for 0.5 h in a water bath at 85°C and stirring at 350 rpm. After complete gelatinization, the mixture was cooled to 45°C, and the pH value was adjusted to 6.2 with a 0.5 mol / L sodium hydroxide solution. Then, 3 parts by mass of copper sulfate and 20 parts by mass of a 30% hydrogen peroxide solution were added, and the mixture was oxidized for 24 h in a water bath at 45°C and mechanically stirred at 300 rpm. After the reaction was completed, the mixture was precipitated with anhydrous ethanol and washed with water, and then diluted and dispersed in deionized water (solid content was 2%), and then homogenized 20 times in an ultra-high pressure nanomaterial preparation disperser to obtain a high cavity nano starch dispersion.

[0084] (2) Preparation of natural latex / starch composites

[0085] 150 parts by mass of 2 wt% high-cavity nano-starch dispersion and 33.4 parts by mass of natural latex with a solid content of 60% were mechanically stirred and blended at room temperature and a rotation speed of 500 rpm for 1 hour to allow the starch to be fully and evenly dispersed in the natural latex, and then the mixture was demulsified, precipitated, washed with water, and dried in a vacuum oven at 50°C for 24 hours to obtain a natural latex / starch composite.

[0086] Comparative Example 1

[0087] 2 parts by mass of pure starch and 33.4 parts by mass of natural latex with a solid content were mechanically stirred at room temperature and a speed of 500 rpm for 1 hour, then demulsified, settled, washed with water and dried in a vacuum oven at 50°C for 24 hours to obtain a natural latex / pure starch complex. When it was mixed with rubber additives using traditional rubber processing technology, it was found that the rubber was tightly adhered to the roller, making it difficult to carry out the mixing operation. Figure 4 This is a photograph of the natural latex / pure starch composite in Comparative Example 1 sticking to the roller during mixing.

[0088] Comparative Example 2

[0089] 33.4 parts by mass of natural latex with a solid content of 60% was mechanically stirred at room temperature and a rotation speed of 500 rpm for 1 hour, then demulsified, precipitated, washed with water, and dried in a vacuum oven at 50° C. for 24 hours to obtain a pure sample of natural latex.

[0090] The natural latex / starch composite obtained in Examples 1-6 and the pure natural latex sample obtained in Comparative Example 2 were first plasticized under cooling water at room temperature, and then mixed in the order of adding stearic acid, zinc oxide, accelerator, and sulfur. Finally, the mixed rubber was thinned 10 times and cut into sheets. After the mixed rubber was mixed and parked overnight, the vulcanization characteristic curve was measured with a vulcanizer, and vulcanization molding was performed with a flat vulcanizer under the vulcanization conditions of 143°C×Tc90. A rubber sample was prepared. The vulcanization formula was (dry basis): 100 parts by mass of natural latex / composite material, 0.4 parts by mass of stearic acid, 1.0 parts by mass of zinc oxide, 0.3 parts by mass of accelerator, and 0.3 parts by mass of sulfur. 0.2 parts by mass of antioxidant was also added to the pure natural latex sample.

[0091] The rubber samples prepared above were aged in a hot oxygen aging oven at 70° C. for 72 h according to GB / T 13939-2014. Dumbbell-shaped tensile specimens and uncut right-angle specimens were cut according to GB / T 528-2009 and GB / T 529-2008 to test tensile properties and tear strength.

[0092] The tensile strength, elongation at break, 100% modulus, 300% modulus and tear strength of the samples before and after aging were statistically analyzed. The statistical results before aging are shown in Table 1, and the statistical results after aging are shown in Table 2.

[0093] Table 1

[0094]

[0095] Table 2

[0096]

[0097] As can be seen from the table, the tensile strength and tear strength of the natural rubber reinforced with the high-cavity nano starch of the present invention are significantly improved. At the same time, the natural rubber reinforced with the high-cavity nano starch of the present invention has a more excellent aging resistance without adding an antioxidant, which not only solves the problem of uneven rubber materials, increased defects, discoloration and environmental pollution caused by the addition of existing antioxidants, but also achieves better aging resistance.

[0098] The above embodiments are preferred implementation modes of the present invention, but the implementation modes of the present invention are not limited to the above embodiments. Any other changes, modifications, substitutions, combinations, and simplifications that do not deviate from the spirit and principles of the present invention should be equivalent replacement methods and are included in the protection scope of the present invention.

Claims

1. A method for preparing high-cavity nano starch, characterized in that The method comprises sequentially performing gelatinization pretreatment and single helix structure modification treatment on starch, and then homogenizing the starch in an ultra-high pressure nano material preparation disperser to obtain high-cavity nano starch.

2. The preparation method according to claim 1, characterized in that: The single helix structure modification treatment includes enzymatic modification, acidic modification or oxidative modification treatment.

3. The preparation method according to claim 2, characterized in that: The enzymatic and acid hydrolysis modification treatment comprises the following steps: adding amylase after starch gelatinization pretreatment, enzymatic hydrolysis at a warm temperature, adding acid solution after heating and inactivation, heating and acid hydrolysis, and obtaining modified starch with a single helical structure after enzymatic and acid hydrolysis.

4. The preparation method according to claim 3, characterized in that: The amount of amylase used is 5-30 ASPU / g starch; the heat preservation enzymolysis is carried out at 55-65°C, and the enzymolysis time is 4-8h; the molar ratio of the acid solution to starch is 0.25:1-1:1; the heated acidolysis is carried out at 70-90°C, and the acidolysis time is 1-6h.

5. The preparation method according to claim 2, characterized in that: The oxidative modification treatment is carried out by subjecting the starch after gelatinization pretreatment to an oxidative reaction with copper sulfate and hydrogen peroxide under acidic conditions.

6. The preparation method according to claim 5, characterized in that: The amount of copper sulfate used is 1-3‰ of the mass of starch; the molar ratio of hydrogen peroxide to starch used is 0.15:1-0.5:

1.

7. A high cavity nano starch, characterized in that Obtained based on the preparation method according to any one of claims 1 to 6.

8. Use of the high-cavity nano-starch according to claim 7 in rubber modification.

9. A natural latex / starch composite, characterized in that The components contain the high-cavity nano-starch described in claim 7.

10. A highly aging-resistant rubber material based on the high-cavity nano-starch according to claim 7, characterized in that The component contains 1-30wt% of high-cavity nano starch.

Citation Information

Patent Citations

  • Preparation method for porous starch / natural rubber compound

    CN102516612A

  • Environmental-friendly technology for synchronously extracting sugar and starch nanocrystallines by using enzymatic method

    CN102965409A

  • Water leakage prevention and aging resistant vacuum flask

    CN104910460A

  • Processing method of lotus seed starch-lipid compound nanoparticles

    CN106832435A

  • Preparation method of starch nanoparticle with controllable morphology and particle size

    CN106883463A